Energy efficiencey in strategy of sustainable production. - Franke, Jorg; Kreitlein, Sven (Applied mechanics and materials ;, 2017)
The Green Factories in Bavaria bundle up the research skills of all relevant fields for energy efficient production, e.g. Mechanical Engineering, Processing Technologies, Electrical Engineering, Information Technology, Process Engineering, Materials Science and Economic Science.